Nutrients Variation in Reclaimed Island of Southern Peninsular Malaysia - Shahri, Zarina; Matias-Peralta, Hazel Monica; Harun, Mazhatarmizi; Gonawan, Nurul Huda (Journal of Science and Technology, 2018)
All living organisms required the nutrients phosphorus and nitrogen for their metabolism, growth and reproduction including seagrass ecosystem. Seagrass required dissolved inorganic nitrogen (N) and phosphorus (P) to maintain growth, where ammonium is considered as the main source of nitrogen, while the main phosphorus sources is phosphate. However, the nutrient cycling process was disturbed by anthropogenic activities. Reclaimed island near to seagrass bed affected the sedimentation and indirectly impacted the nutrient cycling. The purpose of this study is to investigate the nutrient variation in seawater from seagrass meadow. The study was conducted at Merambong seagrass meadow located between the Causeway second link and the Pulau Merambong, Southwest of Johor. Samples were well collected bimonthly from August 2016 until June 2017 and from 10 sampling points. The nutrients studied were including total ammonium nitrogen (TAN), nitrate nitrogen, nitrite nitrogen and soluble reactive phosphorus (SRP). All the nutrients results were compared with Malaysia Marine Water Quality Criteria and Standard (IMWQS). The lowest concentration (2.3 ppb) of nitrite was observed in South area in June 2017 whereas the highest concentration (40.8 ppb). The highest concentration was 32.5 ppb (North) in April 2017 and the lowest concentration was 4.7 ppb in August 2016. In April 2017, low ammonium concentration was 3.5 ppb in North. The highest concentration (57.8 ppb) was detected in North area in October 2016. The highest concentration was detected in North area with 321.8 ppb whereas exceeded the limit (75 ppb) and the lowest concentration was 16.1 ppb in August 2016 of South area. In general, the results of this study show the nutrients concentration in all sampling duration are below the limit lined by IMWQS except for phosphorus concentration detected in June 2017.